Implementasi Multimedia Interaktif PEPAHARI Berbasis Budaya Lokal Kediri untuk Meningkatkan Numerasi Siswa - Friesca Adelia Riyadi; Nurita Primasatya; Kharisma Eka Putri (Lembaga Yasin AlSys, 2026)
The low numeracy skills of elementary school students, particularly in understanding fraction addition and subtraction operations, indicate the need for interactive and contextual learning media. This study aimed to evaluate the effectiveness of PEPAHARI (Addition and Subtraction of Kediri Heritage Fractions) interactive multimedia in improving the numeracy skills of fifth-grade students. The multimedia was developed using Articulate Storyline and integrated visualizations of Kediri local culture in the form of tahu kuning and gethuk pisang to explain fraction concepts concretely. This study employed a one-group pretest–posttest design involving 20 fifth-grade students at SDN Campurejo 2. Data were collected through interviews, observations, and tests. The multimedia was implemented over two sessions using the project-based learning (PjBL) model, while the test data were analyzed descriptively using the N-gain formula. The results showed that the students’ mean score increased from 56 on the pretest to 94.15 on the posttest, with a mean N-gain of 0.87, which was classified as high. These findings indicate that the implementation of PEPAHARI interactive multimedia is potentially effective in improving students’ numeracy skills in fraction addition and subtraction. However, because the improvement in learning outcomes was not tested using inferential statistics, the findings of this study should be interpreted with caution. This study contributes to the development of interactive, contextual, and local culture-based numeracy learning media to support elementary school students’ understanding of fraction concepts.